Programme de développement professionnel des fonctionnaires en vue de la création d’un environnement éducatif sûr dans le cadre de la loi martiale - Iryna Trubavina; Oleksandr Cherednychenko; Kirill Nedria; Nadiia Oliinyk (Éducation et Socialisation)
The relevance of the article is determined by the need to train education managers civil servants and officials of local self-government bodies to work and manage the educational system in war conditions. The purpose of the article is a justification and development of a short-term professional development program for civil servants and officials of local selfgovernment bodies regarding safety in education, creation of a safe educational environment. The research methodology of the article is a complex of scientific approaches that determined the content, methods and form of training: competencebased, axiological, systemic, risk-oriented approaches, public administration approach; approach for human rights. Research methods included analysis of theoretical sources, synthesis, modeling, oral interviews of educators, generalization of experience, and observation. Scientific novelty is substantiated by the content of the program and selection of approaches to learning. Practical significance is the development of a training program for civil servants and officials of local self-government bodies. The results of the study are the content, forms and methods of teaching to solve the education problems under martial law in Ukraine, looking specifically at the example of the Kharkiv region. The new problems of the education organization under the martial law were identified: technical, psychological problems of children and other participants during the educational process, material problems of educational institutions and families, which are necessary to resolve for effective educational process, lack of safety culture among the population, etcetera. The conclusion is that the proposed program answers many questions, especially, for the Kharkiv region and Ukraine. Prospects for further research are expansion of the program content, taking into account the best foreign and Ukrainian experience.